Two distinct effects on neurotransmission in a temperature-sensitive SNAP-25 mutant. - Rao, S.S.; Stewart, B.A.; Rivlin, P.K.; Vilinsky, I.; Watson, B.O.; Lang, C.; Boulianne, G.; Salpeter, M.M.; Deitcher, D.L. (The EMBO Journal, 2001)
Vesicle fusion in eukaryotic cells is mediated by SNAREs (soluble N-ethylmaleimide-sensitive factor attachment protein receptors). In neurons, the t-SNARE SNAP-25 is essential for synaptic vesicle fusion but its exact role in this process is unknown. We have isolated a SNAP-25 temperature-sensitive paralytic mutant in Drosophila, SNAP-25(ts). The mutation causes a Gly50 to Glu change in SNAP-25's first amphipathic helix. A similar mutation in the yeast homologue SEC9 also results in temperature sensitivity, implying a conserved role for this domain in secretion. In vitro-generated 70 kDa SNARE complexes containing SNAP-25(ts) are thermally stable but the mutant SNARE multimers (of approximately 120 kDa) rapidly dissociate at 37 degrees C. The SNAP-25(ts) mutant has two effects on neurotransmitter release depending upon temperature. At 22 degrees C, evoked release of neurotransmitter in SNAP-25(ts) larvae is greatly increased, and at 37 degrees C, the release of neurotransmitter is reduced as compared with controls. Our data suggest that at 22 degrees C the mutation causes the SNARE complex to be more fusion competent but, at 37 degrees C the same mutation leads to SNARE multimer instability and fusion incompetence.